Factors Affecting the Issuance of a Letter of Absolute Liability - Ramelan, Sukma Asmarandani; Kamba, Sri Nanang Meiske (Damhil Law Journal, 2023)
This article analyses the factors behind the government's issuance of a Certificate in Lieu of Birth Certificate and how this measure provides a solution for the legal documentation of children's births, especially in the Bone Bolango Regency. This research is an empirical legal research that is used as a method to study an applicable legal provision, as well as how the realization and reality of these provisions in people''s lives.There is a conflict with each other, so that between these regulations the legal principle can be applied in the form of the principle of lex superior derogat legi inferiori based on this legal principle that higher regulations take precedence over lower regulations in the hierarchy of laws and regulations. So in this case, if there is a conflict between the two regulations, then Law No. 1 of 1974 takes precedence, because in the hierarchical system of laws and regulations, the position of laws is higher than Ministerial regulations.It can be seen that this Letter of Absolute Liability-SPTJM is the basis for issuing birth certificates for children with the mother''s name without a father. Factors that influence the issuance of Letter of Absolute Liability-SPTJM on the issuance of birth certificates for children in siri marriages at the Population and Civil Registry Office of Bone Bolango Regency are (1) Witnesses of unregistered marriages, (2) Difficulties in administering Letter of Absolute Liability-SPTJM, and (3) Impact of Letter of Absolute Liability-SPTJM.